Quality management systems and working capital SMEs in GPO: A case of Poland - Grzegorz Zimon; Dominik Zimon (Administrative Sciences, 2020)
Working capital is designed to provide enterprises with financial security. Its level depends on the strategy of managing individual elements of working capital. An appropriate management strategy allows companies to obtain added working capital. Working capital management is a difficult process as it concerns both current assets and current liabilities. Therefore, company managers are constantly looking for solutions, methods and tools that will help them to manage their working capital. A quality management system is the one that facilitates control over the management of individual elements that create net working capital. The introduction of appropriate procedures derived from quality management systems in specific areas is a great support for creating a positive net working capital. The aim of this paper is to show how the introduction of quality management systems can positively affect the level of working capital. The article presents how quality management systems allow for optimizing the level of individual components, creating a positive net working capital. The research was carried out on a group of 102 Polish small trading companies operating in the same industry. The enterprises were divided into two groups of companies applying the quality management system and of those that did not use such systems. Based on the financial statements for the years 2017-2019 and by means of appropriately selected financial ratios, an analysis of the impact of quality management systems on net working capital was carried out. The results in some areas of management of individual components of net working capital in different groups of enterprises were compared. The research was carried out with the application of appropriate statistical methods. The analysis showed that enterprises using quality management systems managed working capital more efficiently. In the literature, the subject of the impact of quality management systems on working capital is not popular. This paper may be a source for further, extended research and considerations regarding the impact of quality management on the level of working capital in enterprises.
Keywords: 350; working capital; quality; management; small-and medium-sized enterprises; Poland